Method for preparing porous spherical basic magnesium carbonate based on bittern and application of porous spherical basic magnesium carbonate in preparation of flame-retardant synergist

By using micron-level porous spherical magnesium carbonate-loaded nano-level flame retardant synergist, the problem of poor dispersion of nano-level flame retardant is solved, the flame retardant efficiency and the comprehensive performance of the material are improved, and environmentally friendly and efficient flame retardant is achieved. Effect.

CN119263318APending Publication Date: 2025-01-07UNIV OF SCI & TECH OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411390281.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The poor dispersion and easy agglomeration of nano-scale flame retardant synergists in materials lead to low flame retardant efficiency and negative impact on the mechanical properties of materials.

Method used

By using micron-scale porous spherical magnesium carbonate as a carrier, the nano-scale flame retardant synergist is loaded with its large specific surface area and high pore volume, the dispersion of nano-scale particles is improved, and the dispersion of nano-scale particles is improved by simple stirring at room temperature. A porous spherical basic magnesium carbonate-loaded nanoscale flame retardant synergist was prepared.

Benefits of technology

It significantly improves the dispersion and flame retardant efficiency of the flame retardant, reduces the amount of flue gas during combustion, reduces the impact on the mechanical properties of polymer materials, and is simple and environmentally friendly, and meets the standards of modern industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263318A_ABST
    Figure CN119263318A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing porous spherical basic magnesium carbonate based on bittern and application of the porous spherical basic magnesium carbonate in preparation of a flame-retardant synergist. Micron-sized porous spherical basic magnesium carbonate is prepared on the basis of bittern, and the nanoscale flame-retardant synergist is loaded through a simple self-assembly method, so that the problems that the flame-retardant efficiency of basic magnesium carbonate is low and the dispersity of the nanoscale flame-retardant synergist is poor are solved. The prepared flame retardant is simple in reaction process, low in energy consumption, short in consumed time, economical and environmentally friendly, magnesium-containing bittern is subjected to resource utilization again, the dispersity of a nanoscale flame retardant synergist is improved, the problems that a traditional basic magnesium carbonate flame retardant is low in efficiency, and preparation of a hybrid flame retardant is not environmentally friendly are solved, and the flame retardant is suitable for industrial production. And the flame retardant can be widely applied to the fields of chemical engineering, buildings, traffic, machinery and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardants, and particularly relates to a method for preparing porous spherical basic magnesium carbonate based on bittern and application of the method in the preparation of flame retardant synergists. Background Art

[0002] Brine is high-salt wastewater generated during industrial production. Its main hazards include salinization of soil and water bodies, destruction of ecological balance, impact on crop growth, and harm to aquatic organisms. In addition, heavy metals and other harmful substances contained in bittern may accumulate through the food chain, posing a threat to human health. Reasonable treatment and utilization of bittern can not only reduce environmental pressure, but also achieve sustainable development of resources. Therefore, the resource utilization of bittern is of great significance.

[0003] As an important metal element, magnesium has a wide range of applications in the field of flame retardants. Basic magnesium carbonate flame retardant can be extracted and prepared from bittern. In the preparation of basic magnesium carbonate, the reaction conditions can be controlled, and surfactants can be added to adjust the morphology and particle size to meet different needs. The product is flame retardant, dispersible and processable, and easy to mix with the substrate. Basic magnesium carbonate flame retardant is non-toxic, decomposes under heat to produce non-flammable gas, dilutes combustible gas and reduces combustion temperature. It is widely used in plastics, rubber, coatings and other fields to improve the flame retardant properties of materials and ensure product safety. However, the flame retardant efficiency of basic magnesium carbonate is low, and it can be used in conjunction with other flame retardants to enhance the flame retardant effect.

[0004] Flame retardant synergists can work synergistically with the main flame retardant to significantly improve the flame retardant properties of the material. The main problems faced by nano-scale flame retardant synergists in application are uneven dispersion and easy agglomeration. This phenomenon is due to the extremely high surface energy of nano-scale particles, which leads to strong surface polarity and easy mutual attraction and aggregation into larger particle clusters. Not only will it affect the uniform distribution of flame retardant synergists in the matrix material, but it may also reduce the flame retardant effect and mechanical properties of polymer materials.

[0005] In order to solve the problems of uneven dispersion and easy agglomeration of nano-scale flame retardant synergists, a variety of strategies can be adopted. Through surface modification, the surface properties of nanoparticles can be changed, their surface energy can be reduced, thereby reducing the interaction force between particles and improving their dispersibility and stability in the matrix material. Specific methods include coating treatment modification, precipitation reaction modification, surface chemical modification, mechanochemical modification, high-energy treatment modification, microencapsulation modification, etc. In addition, physical or chemical methods can be used to promote the dispersion of nano-scale flame retardant synergists in the matrix material, such as using the masterbatch method to improve the preparation efficiency and quality. Traditional nano-scale flame retardant synergists may require complex steps and conditions during the preparation process, resulting in a long time, low efficiency, and possible environmental problems. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing porous spherical basic magnesium carbonate based on bittern and its application in the preparation of flame retardant synergists, so as to solve the problems of low flame retardant efficiency of basic magnesium carbonate and poor dispersibility of nano-scale flame retardant synergists.

[0007] The micron-sized porous spherical basic magnesium carbonate prepared by the present invention based on bittern shows its unique advantages, which are specifically manifested in its significant specific surface area advantage and excellent adsorption capacity, and opens up a new path for the application in the field of flame retardant materials. The present invention uses micron-sized porous spherical basic magnesium carbonate as a carrier to load nano-sized flame retardant synergists, effectively solving the dispersion problem of nano-sized flame retardants in materials, enhancing the compatibility of flame retardants with matrix materials, significantly improving the overall flame retardant properties of the material, and minimizing the impact on the mechanical properties and comprehensive properties of the material.

[0008] The method for preparing porous spherical basic magnesium carbonate based on bittern comprises the following steps:

[0009] 30-45 g of bittern with a magnesium content of 25%-30% is used, water is added to prepare a 100 mL solution, 0.4-0.5 g of sodium dodecylbenzene sulfonate is added as a modifier, 100-200 mL of a solution containing 25.44-28 g of sodium carbonate is added at 60-80° C. and stirred for 60-90 seconds, then pyrolyzed at 110-130° C. for 1-3 hours, aged overnight, filtered, washed and dried to obtain micron-sized porous spherical basic magnesium carbonate.

[0010] The porous spherical basic magnesium carbonate of the present invention is used in the preparation of the flame retardant synergist. The porous spherical basic magnesium carbonate is used as a carrier to load the nano-scale flame retardant synergist, so as to solve the dispersion problem of the nano-scale flame retardant synergist and improve the flame retardant efficiency of the basic magnesium carbonate. At the same time, the release of toxic smoke when the polymer composite material is burned can be reduced.

[0011] The specific steps include:

[0012] 1-30 parts of nano-scale flame retardant synergist are dispersed in 300-400 parts of water, and ultrasonically dispersed for 10-150 minutes. Then, 70-99 parts of micron-scale porous spherical basic magnesium carbonate are added, and stirred at room temperature for 10-60 minutes. The mixture is filtered, washed and vacuum dried in sequence to obtain micron-scale porous spherical basic magnesium carbonate loaded with nano-scale flame retardant synergist.

[0013] The nano-scale flame retardant synergist is selected from one or more of cuprous oxide, cupric oxide, cobalt oxide, lanthanum oxide, cerium oxide, titanium dioxide, silicon dioxide, zinc hydroxystannate, copper hydroxystannate, cerium stannate, lanthanum stannate, gadolinium stannate, samarium stannate, and neodymium stannate and mixed in any proportion.

[0014] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0015] 1. The present invention has significant environmental benefits: bittern is high-salt wastewater generated in the industrial production process. Its main hazards include salinization of soil and water bodies, destruction of ecological balance, and influence on crop growth, which is a major hazard to the environment. In addition, the preparation process of nano-scale flame retardant synergist solvent masterbatch requires complex steps and conditions, resulting in a long time, high power consumption, low efficiency, and the use of solvents, which pollutes the environment. The present invention extracts magnesium from bittern and converts it into a basic magnesium carbonate flame retardant, and utilizes micron-level porous spherical basic magnesium carbonate to become an ideal adsorption carrier by virtue of its large specific surface area and high pore volume. Under room temperature conditions, porous spherical basic magnesium carbonate loaded nano-scale flame retardant synergist can be prepared by a simple stirring method. The method is simple, the process is simple, and it is non-toxic and harmless, which meets the strict standards of modern industry for environmental protection and safety; it not only eliminates the pollution of bittern and the preparation of nano masterbatch, but also promotes the recycling of resources and promotes the sustainable development of the economy.

[0016] 2. The present invention can significantly improve the flame retardant effect: the porous spherical basic magnesium carbonate loaded nano-level flame retardant synergist significantly improves the dispersion uniformity of the nano-level flame retardant synergist in the polymer composite material, and can play a synergistic flame retardant role with basic magnesium carbonate, further improving the flame retardant efficiency of basic magnesium carbonate, improving the flame retardant level in the polymer material, and reducing the amount of smoke generated during combustion; the well-dispersed flame retardant can reduce the impact on the mechanical properties of the polymer material, and improve the mechanical properties and comprehensive physical properties of the flame retardant polymer material. It shows a broad market application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM test characterization diagram of BMC in Example 1.

[0018] Figure 2 The BMC@Cu in Example 1 2 O SEM test characterization picture.

[0019] Figure 3 The BMC@Cu in Example 1 2 O XRD test characterization diagram.

[0020] Figure 4 The BMC@Cu in Example 1 2 O's Mapping test representation diagram.

[0021] Figure 5 This is a SEM test characterization diagram of BMC in Example 2.

[0022] Figure 6 It is BMC@ZnSn(OH) in Example 26 SEM test characterization diagram.

[0023] Figure 7 It is BMC@ZnSn(OH) in Example 2 6 XRD test characterization diagram.

[0024] Figure 8 It is BMC@ZnSn(OH) in Example 2 6 Mapping test characterization diagram.

[0025] Fig. 9 This is a SEM test characterization diagram of BMC in Example 3.

[0026] Fig.10 is the BMC@Ce in Example 3 2 Sn 2 O 7 SEM test characterization diagram.

[0027] Fig.11 is the BMC@Ce in Example 3 2 Sn 2 O 7 XRD test characterization diagram.

[0028] Fig.12 is the BMC@Ce in Example 3 2 Sn 2 O 7 Mapping test characterization diagram. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further analyzed and explained below through specific embodiments.

[0030] The micron-sized porous spherical basic magnesium carbonate of the present invention is loaded with a nano-sized flame retardant synergist, and the nano-sized flame retardant synergist is combined with the micron-sized spherical basic magnesium carbonate by direct stirring and self-assembly in an aqueous solution.

[0031] Embodiment 1:

[0032] 1. The preparation method of micron-sized porous spherical basic magnesium carbonate (BMC) is as follows:

[0033] Use 40.7g of bittern with a magnesium content of 25% to prepare 100ml of solution, add 0.45g of sodium dodecylbenzene sulfonate as a modifier, add 100ml of a solution prepared with 25.44g of sodium carbonate at 60°C, stir rapidly for 60s, then pyrolyze at 110°C for 1h, age overnight, filter, wash, and dry to obtain micron-sized porous spherical basic magnesium carbonate (BMC).

[0034] 2. Porous spherical basic magnesium carbonate loaded with nano-sized cuprous oxide (BMC@Cu 2 O) The preparation method of the flame retardant synergist is as follows:

[0035] 1 part of nano-sized cuprous oxide (Cu 2 O) was dispersed in 300 parts of water, ultrasonically dispersed for 10 minutes, and then 99 parts of micron-sized porous spherical basic magnesium carbonate were added, stirred at room temperature for 10 minutes, and then filtered, washed, and vacuum dried to obtain porous spherical basic magnesium carbonate loaded with nano-sized cuprous oxide (BMC@Cu 2 O) Flame retardant synergist.

[0036] To further verify the performance of basic magnesium carbonate @ cuprous oxide flame retardant, we designed a comparative formula as shown in Table 1 to compare the comprehensive physical property test results of the two. The vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formula are shown in Table 2.

[0037] Table 1 Addition amount of each component in the mixing formula

[0038]

[0039] Table 2 Vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formulation

[0040]

[0041] Embodiment 2:

[0042] 1. The preparation method of micron-sized porous spherical basic magnesium carbonate (BMC) is as follows:

[0043] 36.33 g of bittern with a magnesium content of 28% was used to prepare 100 ml of solution, 0.4 g of sodium dodecylbenzene sulfonate was added as a modifier, 200 ml of a solution prepared with 25.44 g of sodium carbonate was added at 70°C, and then the mixture was rapidly stirred for 75 seconds, and then pyrolyzed at 120°C for 2 hours, aged overnight, filtered, washed, and dried to obtain micron-sized porous spherical basic magnesium carbonate (BMC).

[0044] 2. Porous spherical basic magnesium carbonate loaded with nano-sized zinc hydroxystannate (BMC@ZnSn(OH) 6 ) The flame retardant synergist preparation method is as follows:

[0045] 3 parts of nano-sized zinc hydroxystannate (ZnSn(OH) 6) was dispersed in 350 parts of water, ultrasonically dispersed for 30 minutes, and then 97 parts of micron-sized porous spherical basic magnesium carbonate were added, stirred at room temperature for 30 minutes, and then filtered, washed, and vacuum dried to obtain porous spherical basic magnesium carbonate-loaded nano-sized zinc hydroxystannate (BMC@ZnSn(OH) 6 ) Flame retardant synergist.

[0046] To further verify the performance of basic magnesium carbonate @ zinc hydroxystannate flame retardant, we designed a comparative formula as shown in Table 3 to compare the comprehensive physical property test results of the two. Table 4 shows the vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formula.

[0047] Table 3 Addition amount of each component in the mixing formula

[0048]

[0049] Table 4 Vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formulation

[0050]

[0051] Embodiment 3:

[0052] 1. The preparation method of micron-sized porous spherical basic magnesium carbonate (BMC) is as follows:

[0053] 34 g of bittern with a magnesium content of 30% was used to prepare a 100 ml solution, 0.5 g of sodium dodecylbenzene sulfonate was added as a modifier, and 100 ml of a solution prepared with 28 g of sodium carbonate was added at 80°C, and then rapidly stirred for 90 seconds, and then pyrolyzed at 130°C for 3 hours, aged overnight, filtered, washed, and dried to obtain micron-sized porous spherical basic magnesium carbonate (BMC).

[0054] 2. Porous spherical basic magnesium carbonate loaded with nano-sized cerium stannate (BMC@Ce 2 Sn 2 O 7 ) The flame retardant synergist preparation method is as follows:

[0055] 5 parts of nano-sized cerium stannate (Ce 2 Sn 2 O 7 ) was dispersed in 400 parts of water, ultrasonically dispersed for 150 minutes, and then 95 parts of micron-sized porous spherical basic magnesium carbonate were added, stirred at room temperature for 60 minutes, and then filtered, washed, and vacuum dried to obtain porous spherical basic magnesium carbonate loaded with nano-sized cerium stannate (BMC@Ce 2 Sn 2 O7 ) Flame retardant synergist.

[0056] To further verify the performance of basic magnesium carbonate @ cerium stannate flame retardant, we designed a comparative formula as shown in Table 5 to compare the comprehensive physical property test results of the two. Table 6 shows the vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formula.

[0057] Table 5 Addition amount of each component in the mixing formula

[0058]

[0059] Table 6 Vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formulation

[0060]

[0061] Embodiment 4:

[0062] 1. The preparation method of micron-sized porous spherical basic magnesium carbonate (BMC) is as follows:

[0063] Use 40.7g of bittern with a magnesium content of 28% to make 100ml, add 0.45g of sodium dodecylbenzene sulfonate as a modifier, add 100ml of a solution made with 25.44g of sodium carbonate at 60°C, stir rapidly for 60s, then pyrolyze at 130°C for 1h, age overnight, filter, wash, and dry to obtain micron-sized porous spherical basic magnesium carbonate (BMC).

[0064] 2. The preparation method of porous spherical basic magnesium carbonate loaded nano-scale copper oxide flame retardant synergist (BMC@CuO) is as follows:

[0065] 30 parts of nano-copper oxide (CuO) were dispersed in 300 parts of water and ultrasonically dispersed for 100 minutes. Then, 70 parts of micron-sized porous spherical basic magnesium carbonate were added and stirred at room temperature for 10 minutes. The mixture was then filtered, washed and vacuum dried to obtain a porous spherical basic magnesium carbonate-loaded nano-copper oxide (BMC@CuO) flame retardant synergist.

[0066] To further verify the performance of basic magnesium carbonate @ copper oxide flame retardant, we designed a comparative formula as shown in Table 7 to compare the comprehensive physical property test results of the two. Table 8 shows the vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formula.

[0067] Table 7 Addition amount of each component in the mixing formula

[0068]

[0069] Table 8 Vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formulation

[0070]

[0071] Embodiment 5:

[0072] 1. The preparation method of micron-sized porous spherical basic magnesium carbonate (BMC) is as follows:

[0073] 36.33 g of bittern with a magnesium content of 25% was used to prepare 100 ml of solution, 0.4 g of sodium dodecylbenzene sulfonate was added as a modifier, 25.44 g of sodium carbonate was added to prepare 200 ml of solution at 70°C, and then the solution was rapidly stirred for 75 seconds, and then pyrolyzed at 110°C for 3 hours, aged overnight, filtered, washed, and dried to obtain micron-sized porous spherical basic magnesium carbonate (BMC).

[0074] 2. Porous spherical basic magnesium carbonate loaded with nano-sized copper hydroxystannate (BMC@CuSn(OH) 6 ) The flame retardant synergist preparation method is as follows:

[0075] 20 parts of nano-sized copper hydroxystannate (CuSn(OH) 6 ) was dispersed in 350 parts of water, ultrasonically dispersed for 10 minutes, and then 80 parts of micron-sized porous spherical basic magnesium carbonate were added, stirred at room temperature for 30 minutes, and then filtered, washed, and vacuum dried to obtain porous spherical basic magnesium carbonate-loaded nano-sized copper hydroxystannate (BMC@CuSn(OH) 6 ) Flame retardant synergist.

[0076] To further verify the performance of basic magnesium carbonate @ hydroxy copper stannate flame retardant, we designed a comparative formula as shown in Table 9 to compare the comprehensive physical property test results of the two. Table 10 shows the vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formula.

[0077] Table 9 Addition amount of each component in the mixing formula

[0078]

[0079] Table 10 Vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formulation

[0080]

[0081] Embodiment 6:

[0082] 1. The preparation method of micron-sized porous spherical basic magnesium carbonate (BMC) is as follows:

[0083] 34 g of bittern with a magnesium content of 28% was used to prepare a 100 ml solution, 0.5 g of sodium dodecylbenzene sulfonate was added as a modifier, 28 g of sodium carbonate was added to prepare a 100 ml solution at 80 ° C, and then the solution was rapidly stirred for 90 seconds, then pyrolyzed at 120 ° C for 2 hours, aged overnight, filtered, washed, and dried to obtain micron-sized porous spherical basic magnesium carbonate (BMC).

[0084] 2. Porous spherical magnesium carbonate loaded with nano-sized lanthanum stannate (BMC@La 2 Sn 2 O 7 ) The flame retardant synergist preparation method is as follows:

[0085] 25 parts of nano-sized lanthanum stannate (La 2 Sn 2 O 7 ) was dispersed in 400 parts of water, ultrasonically dispersed for 120 minutes, and then 75 parts of micron-sized porous spherical basic magnesium carbonate were added, stirred at room temperature for 30 minutes, and then filtered, washed, and vacuum dried to obtain porous spherical basic magnesium carbonate loaded with nano-sized lanthanum stannate (BMC@La 2 Sn 2 O 7 ) Flame retardant synergist.

[0086] To further verify the performance of tin basic magnesium carbonate @ acid cerium lanthanide flame retardant, we designed a comparative formula as shown in Table 11 to compare the comprehensive physical property test results of the two. Table 12 shows the vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formula.

[0087] Table 11 Addition amount of each component in the mixing formula

[0088]

[0089] Table 12 Vertical combustion (UL-94), limiting oxygen index (LOI), mechanical properties, combustion performance (Cone) and smoke density test results of the materials obtained from each formulation

[0090]

[0091] In the above examples, a range of values ​​was explored to achieve the stability of the morphology of spherical basic magnesium carbonate, that is, it would not affect the mechanical properties of the material too much, nor would it cause agglomeration in the material due to too small a size. At present, the BET specific surface area value of spherical basic magnesium carbonate is approximately regulated at 35 m2 / g. When the ratio of magnesium content to sodium carbonate content changes, and when the type and amount of modifier added change, the morphology will change to rod-like, flake-like, etc. The stirring time and pyrolysis time directly affect the size of the sphere and the integrity of the spherical morphology. The present invention regulates the pore size on the spherical basic magnesium carbonate in order to just adsorb enough nano-scale flame retardant synergists, which is also mainly determined according to the specific sizes of different nano-scale flame retardant synergists, which is intuitively reflected in the SEM image.

[0092] Based on the above experimental results, the following conclusions are drawn:

[0093] (1) By extracting magnesium from bittern and converting it into basic magnesium carbonate flame retardant, and utilizing its large specific surface area and high pore volume, porous spherical basic magnesium carbonate loaded nano-scale flame retardant synergist was prepared. This method is simple, non-toxic and harmless, not only eliminates pollution, but also promotes resource recycling and promotes sustainable development.

[0094] (2) The invention significantly enhances the flame retardant effect, improves the dispersibility of nano flame retardant synergists in polymer composite materials, improves the flame retardant level, reduces smoke volume, reduces the impact on the mechanical properties of polymer materials, and improves the comprehensive physical properties of materials, and has broad market application potential.

[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing porous spherical basic magnesium carbonate based on bittern, characterized in that The steps include: Bitter brine with a magnesium content of 25%-30% is used, water is added to prepare a solution, sodium dodecylbenzene sulfonate is added as a modifier, sodium carbonate solution is added at 60-80°C and stirred for 60-90s, then pyrolyzed and aged, filtered, washed and dried to obtain micron-sized porous spherical basic magnesium carbonate.

2. The method according to claim 1, characterized in that: 30-45 g of bittern with a magnesium content of 25%-30% is used, water is added to prepare a 100 mL solution, 0.4-0.5 g of sodium dodecylbenzene sulfonate is added as a modifier, 100-200 mL of a solution containing 25.44-28 g of sodium carbonate is added at 60-80° C. and stirred for 60-90 seconds, followed by pyrolysis and aging, and filtering, washing and drying to obtain micron-sized porous spherical basic magnesium carbonate.

3. The method according to claim 2, characterized in that: The pyrolysis temperature is 110-130°C, and the pyrolysis time is 1-3h.

4. Use of the porous spherical basic magnesium carbonate prepared according to claim 1, 2 or 3 in the preparation of a flame retardant synergist.

5. The use according to claim 4, characterized in that: The porous spherical basic magnesium carbonate is used as a carrier to load a nano-scale flame retardant synergist to solve the dispersion problem of the nano-flame retardant synergist and improve the flame retardant efficiency of the basic magnesium carbonate, while also reducing the release of toxic smoke when the polymer composite material is burned.

6. The use according to claim 5, characterized in that: 1-30 parts of nano-scale flame retardant synergist are dispersed in 300-400 parts of water, and ultrasonically dispersed for 10-150 minutes. Then, 70-99 parts of micron-scale porous spherical basic magnesium carbonate are added, and stirred at room temperature for 10-60 minutes. The mixture is filtered, washed and vacuum dried in sequence to obtain micron-scale porous spherical basic magnesium carbonate loaded with nano-scale flame retardant synergist.

7. The use according to claim 5, characterized in that: The nano-scale flame retardant synergist is selected from one or more of cuprous oxide, cupric oxide, cobalt oxide, lanthanum oxide, cerium oxide, titanium dioxide, silicon dioxide, zinc hydroxystannate, copper hydroxystannate, cerium stannate, lanthanum stannate, gadolinium stannate, samarium stannate, and neodymium stannate and mixed in any proportion.